Direct Visualization of Model Membrane Remodeling by α‐Synuclein Fibrillization - Chaudhary, Himanshu (Chemphyschem, 2017)
The interaction of α‐synuclein (αS) with membranes is thought to be critical in the etiology of Parkinson's disease. Besides oligomeric αS aggregates that possibly form membrane pores, the aggregation of αS into amyloid fibrils has been reported to disrupt membranes. The mechanism by which aggregation affects the integrity of membranes is, however, unknown. Here, we show that whereas mature αS fibrils only weakly adhere to POPC/POPG giant unilamellar vesicles (GUVs), fibrillization of αS on the membrane results in large‐scale membrane remodeling. Fibrils that grow on the vesicle surface stiffen the membrane and make the initially spherical membrane become polyhedral. Additionally, membrane‐attached fibrils extract lipids. The lipid extraction and membrane remodeling of growing fibrils can consume the complete bilayer surface and results in loss of vesicle content. These observations suggest that there are several mechanisms by which growing fibrils can disrupt membrane function.